Ramón Castilla y Marquesado:: un personaje recurrente en las Tradiciones de Palma - Adriazola Silva, Juan Carlos (2018)
Military leaders in the history of Peru during the nineteenth century have left an indelible mark on the national conscience, but none with the peculiar characteristics of the great marshal Don Ramon Castilla y Marquesado, Who made strenuous efforts to establish in its various governments the political, legislative and economic order that the country needed, which turned him into a statesman of the highest order and led the peruvian nation to an unexpected boom. This communication seeks to find the connections that this caudillo has with another great Peruvian: Don Ricardo Palma Soriano, the Father of Traditions. It tries to explain, as well, why the traditionist founded in Castilla an ideal person to relate traditions.